2010
DOI: 10.1108/17590831011082437
|View full text |Cite
|
Sign up to set email alerts
|

Arabian Gulf innovator attitudes for online Islamic bank marketing strategy

Abstract: Purpose -This paper's aim is to guide online Islamic bank marketing strategy. Design/methodology/approach -A study in 1999 interviewed 120 innovators about their attitudes and preferences to a hypothetical online Islamic bank, and replicated in 2009 for existing online Islamic banks using a sample of 220 innovators. Findings -The ten-year replication interval reveals increased internet and online bank usage, higher household incomes and concerns about security (fraud, theft, and hacking). Criteria describing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…For this research, the term Islamic finance includes, Islamic banking and financial services, sharia-compliant investment products, and Sukuk (Islamic bonds). Because of the global expansion and growth of Islamic finance, the literature on this topic is rather rich (e.g., Janahi and Mubarak 2017; Dariyoush and Hussin 2016;Fang 2016;Setyobudi et al 2016;Malik et al 2011;Elbeck and Dedoussis 2010). More than 100 Islamic banks now exist in over 35 Muslim and non-Muslim countries alike (Ariff and Rosly 2011).…”
Section: Islamic Financial Service Sectormentioning
confidence: 99%
“…For this research, the term Islamic finance includes, Islamic banking and financial services, sharia-compliant investment products, and Sukuk (Islamic bonds). Because of the global expansion and growth of Islamic finance, the literature on this topic is rather rich (e.g., Janahi and Mubarak 2017; Dariyoush and Hussin 2016;Fang 2016;Setyobudi et al 2016;Malik et al 2011;Elbeck and Dedoussis 2010). More than 100 Islamic banks now exist in over 35 Muslim and non-Muslim countries alike (Ariff and Rosly 2011).…”
Section: Islamic Financial Service Sectormentioning
confidence: 99%
“…Studying consumer perception is the most popular approach to know their motivation, attitude, and behaviour towards IB products and services. Giving account of a number of consumer perception studies, Elbeck and Dedoussis (2010) conclude that consumer preferences for Islamic banks are culturally sensitive, driven by a variety of factors, which could differ from countries to countries; e.g. employees' skills and values (UAE); timeliness, cooperation and financial services (Malaysia); image, confidentiality and reputation (Jordan); and service quality (Turkey).…”
Section: Islamic Banking In Omanmentioning
confidence: 99%
“…The leasing-based Ijarah is used to generally finance the consumer products and vehicles. Elbeck and Dedoussis (2010) described that customer preferences of Islamic banks are based upon a variety of factors which may differ from country to country and Shome et al (2018) also elucidated several factors that customers ponder while dealing with an Islamic bank. Besides the fact that religious beliefs are a major reason to transact with Islamic banks as concluded in different studies (Ringim, 2014;Souiden and Rani, 2015); yet this is also a fact concluded in several past studies that religion is not the single motive of Islamic banking customers (Erol and EI-Bdour, 1989;.…”
Section: Literature Reviewmentioning
confidence: 99%